Milk it for all you can - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The growth of the dairy sector in many ACP countries, welcome as it is in terms of producers income and consumers nutrition, is full of challenges. Among them are issues of marketing, regularity of supplies from producers and delivery to...